1985
DOI: 10.1677/joe.0.1070211
|View full text |Cite
|
Sign up to set email alerts
|

Influences of thyroidectomy and thyroxine replacement on photoperiodically controlled reproduction in quail

Abstract: The breeding season in quail ends when they become relatively refractory to long photoperiods. The processes underlying the development of this refractoriness are dependent upon the thyroid gland. Thyroidectomized male Japanese quail transferred from short (8 h light: 16 h darkness; 8L: 16D) to long (20L:4D) daily photoperiods mature their gonads and develop the androgen-dependent cloacal gland at rates only marginally slower than controls. However, when the birds are retransferred to short days thyroidectomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 0 publications
3
44
0
Order By: Relevance
“…In birds which are long day breeders, thyroidectomy prevents refractoriness developing, and this results in the birds remaining in a breeding condition indefinitely under long days [22][23][24]. In rats, previous studies have shown that hypothyroidism decreases the plasma concentrations of LH and FSH [25,26] and reduces the number and size of gonadotropes [27], suggesting that hypothyroidism is associated with gonadal dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In birds which are long day breeders, thyroidectomy prevents refractoriness developing, and this results in the birds remaining in a breeding condition indefinitely under long days [22][23][24]. In rats, previous studies have shown that hypothyroidism decreases the plasma concentrations of LH and FSH [25,26] and reduces the number and size of gonadotropes [27], suggesting that hypothyroidism is associated with gonadal dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in birds support the hypothesis that the thyroid axis plays a permissive role in the reproduction of seasonally breeding species [11][12][13]. Therefore, the aim of this study was to investigate the effects of hypothyroidism on the adrenal and gonadal functions in adult male Japanese quail.…”
mentioning
confidence: 94%
“…For example, thyroidecAccepted March 23, 1993. Received December 15, 1992 tomy before the onset of the breeding season blocks the transition into the nonbreeding season in certain birds [10][11][12], sheep [13][14], and deer [15]. After thyroidectomy, such animals are maintained in a state of continuous reproductive activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, removal of the thyroid gland prevents seasonal development/regression of gonads in several avian species and in sheep (Moenter et al 1991, Dawson 1993, 1998, Parkinson & Follett 1995. Administration of TH ameliorates the effect of thyroidectomy and mimics exposure to light conditions that induce gonadal development (Follett & Nicholls 1985, Goldsmith & Nicholls 1992, Wilson & Reinert 2000.…”
Section: Roles and Metabolic Pathway Of Thyroid Hormonementioning
confidence: 99%